Malaria community health workers in Myanmar: a cost analysis. (December 2016) - Kyaw, Shwe; Drake, Tom; Thi, Aung; Kyaw, Myat; Hlaing, Thaung; Smithuis, Frank; White, Lisa; Lubell, Yoel
Abstract Background Myanmar has the highest malaria incidence and attributed mortality in South East Asia with limited healthcare infrastructure to manage this burden. Establishing malaria Community Health Worker (CHW) programmes is one possible strategy to improve access to malaria diagnosis and treatment, particularly in remote areas. Despite considerable donor support for implementing CHW programmes in Myanmar, the cost implications are not well understood. Methods An ingredients based micro-costing approach was used to develop a model of the annual implementation cost of malaria CHWs in Myanmar. A cost model was constructed based on activity centres comprising of training, patient malaria services, monitoring and supervision, programme management, overheads and incentives. The model takes a provider perspective. Financial data on CHWs programmes were obtained from the 2013 financial reports of the Three Millennium Development Goal fund implementing partners that have been working on malaria control and elimination in Myanmar. Sensitivity and scenario analyses were undertaken to outline parameter uncertainty and explore changes to programme cost for key assumptions. Results The range of total annual costs for the support of one CHW was US 966–2486. The largest driver of CHW cost was monitoring and supervision (31–60 % of annual CHW cost). Other important determinants of cost included programme management (15–28 % of annual CHW cost) and patient services (6–12 % of annual CHW cost). Within patient services, malaria rapid diagnostic tests are the major contributor to cost (64 % of patient service costs). Conclusion The annual cost of a malaria CHW in Myanmar varies considerably depending on the context and the design of the programme, in particular remoteness and the approach to monitoring and evaluation. The estimates provide information to policy makers and CHW programme planners in Myanmar as well as supporting economic evaluations of their cost-effectiveness.